Establishment of optimal decellularization conditions using porcine placenta - Ji Hyung Son; Dae-Jung Kim; Dong-Mok Lee; Byoung Boo Seo (Journal of Animal Reproduction and Biotechnology, 2021)
Organ transplantation is currently the most fundamental treatment for organ failure, but there is a shortage of organ supply compared to those in need. Regenerative medicine has recently developed a decellularization technique that overcomes the limitations of conventional organ transplantation and attempts to reconstruct damaged tissues or organs to their normal state. Several decellularization methods have been suggested. In this experiment, the decellularization methods were used to find effective decellularization methods for humanlike porcine placenta. The optimal conditions for decellular support are low DNA content and high glycos amino glycans (GAGs) and collagen content. In order to satisfy this condition, SDS and Triton X-100 and SDS + Triton X-100 were used as the detergent used for decellularization in this experiment. The contents were compared according to the decellularization time (0, 12, 24, 48 and 72 hours), and the concentrations of SDS (0.2, 0.5, 0.7 and 1.0%) were mixed in 1.0% Triton X-100 to analyze the contents. When decellularized using SDS and Triton X-100, respectively, it was confirmed that the contents of DNA and GAGs were opposite to each other. And decellularization treatment for 24 hours at 0.5% SDS was able to obtain an effective decellular support. If decellularization studies of various detergents can be obtained an effective decellular support, and furthermore, cell culture experiments can confirm the effect on the cells.